منهج الإمام القنازعي في كتابه " تفسير الموطأ " - بحة, أيوب (University of Eloued جامعة الجزائر, 2020)
اهتم علماء الأندلس بخدمة كتب السُّنة، وعكفوا على دراستها؛ شرحا، وبيانا لأحكامها، وتوضيحا لغريبها، وكلاما في أسانيدها، فكان من أوفر الكتب حظا بالعناية؛ كتاب الموطأ للإمام مالك بن أنس –رحمهما الله- بل لم يحظ كتاب من كتب السُّنة بالخدمة والعناية مثلما حظي به الموطأ، فأوسعوه شرحا ودراسة، وإلى غير ذلك من مظاهر العناية، وكان من أبرز علماء الأندلس الذين اهتموا بخدمة هذا الكتاب؛ الإمام عبد الرحمان بن مروان القُنازعي (413ه)، فألَّف في شرح الموطأ كتابا سماه (تفسير الموطأ)، جمع فيه ما أخذه تلقيًا عن شيوخه، وكذلك ما نقله من الكتب التي توفرت له في زمانه، وقد قامت هذه الدراسة على إبراز معالم منهج الإمام القُنازعي في كتابه تفسير الموطأ، والذي ظهرت فيه خدمته لكتاب الموطأ من جوانب مختلفة، حيث عالج –أثناء تعرضه لأحاديث الموطأ- كثيرا من مباحث علوم رواية الحديث؛ كمسائل الاتصال والانقطاع، أو نقد الرواة والمرويات، وغير ذلك من علوم الرِّواية، لكن الحظ الأوفر من الخدمة لكتاب الموطأ كان قد أَوْلاه لمباحث علوم الدِّراية، وبالأخص معالجته للمسائل الفقهية؛ ولهذا احتوى هذا الكتاب ثروة فقهية عظيمة. فهكذا جاءت عناية الإمام القُنازعي بكتاب الموطأ خصوصا، وبالمذهب المالكي عموما، وسيتضح الأمر أكثر في متن الرسالة –إن شاء الله-.Scholars of Andalusia were interested in serving the books of the Sunnah. They studied them by explaining and showing their rulings, and clarifying their strangeness and their words in the chain of narrators. One of the most privileged books was the book of Al-Muwatta by Imam Malik bin Anas, may Allah have mercy upon them. No other book of the Sunnah received the service and care that the Muwatta had received. They covered it with much explanation, study and so forth of the other aspects of care. Among the most prominent scholars of Andalusia who were interested in serving this book was Imam Abd Al-Rahman bin Marwan Al-Qonazai (413 AH). He wrote a commentary on Al-Muwatta entitled "Interpretation of Al-Muwatta" in which he collected what he orally received from his tutors, as well as what he transmitted from the books that were available to him in his time. This current study is based on highlighting the features of the Imam Al-Qunazi's approach through his book "Interpretation of Al-Muwatta", in which his service to Al-Muwatta’s book appeared in various aspects. While dealing with Al-Muwatta’s Hadiths, he tackled many of the topics of the science of Hadith narration; such as issues of communication and discontinuity, criticism of narrators and narrations, and other sciences of Hadith narration. However, the lion's share of attention for the book of Al-Muwatta was given to the chapters of the science of Deraya (i.e. knowledge), especially his treatment of jurisprudential issues. That is why this book contained a great jurisprudential wealth. This is how the attention of Imam Al-Qonazai appeared particularly in the book of Al-Muwatta, and in the Maliki school in general. This shall be further clarified in the sections of this dissertation, if Allah is willing.
مذكرة ماستر تخصص الحديث وعلومه
Keywords: القُنازعي/ تفسير الموطأ/منهج الإمام القُنازعي; Al-Qonazai/Interpretation of Al-Muwatta/ the features of the Imam Al-Qunazi's